Resveratrol Alleviates Inflammatory Response Through P2X7/NLRP3 Signaling Pathway: In Silico and In Vitro Evidence from Activated Microglia - Bianca Fagan Bissacotti; Marcylene Vieira da Silveira; Charles Elias Assmann; Priscila Marquezan Copetti; André Flores dos Santos; Solange Binotto Fagan; João Augusto Pereira da Rocha; Maria Rosa Chitolina Schetinger; Vera Maria Melchiors Morsch; Nathieli Bianchin Bottari; Alencar Kolinski Machado; Aleksandro Schafer da Silva (Pharmaceuticals, 2025)
Background/Objectives: Chronic inflammation and inappropriate NLRP3 inflammasome regulation are related to many brain diseases. Purinergic mediators may play an important role in inflammation regulation and could be targeted for effective therapies for these illnesses. We evaluated resveratrol’s anti-neuroinflammatory potential in BV-2 microglia cells using an innovative in vitro method of NLRP3 inflammasome activation, correlating with the P2X7 purinergic receptor. Methods: In silico analyses were used to estimate resveratrol’s interaction with NLRP3, and its cytotoxicity was measured for 24, 48, and 72 h. Moreover, microglia were exposed to lipopolysaccharide and nigericin to activate the NLRP3 inflammasome and treated with resveratrol between these inflammatory agents. Results: It was found that resveratrol has binding compatible with modulating NLRP3. Specifically, 0.1–25 µM of resveratrol presented a favorable safety profile in BV-2 cells. Microglia exposed to the inflammatory agents had increased levels of oxidative species, the P2X7 receptor, and pro-inflammatory cytokines. However, resveratrol decreased the NLRP3, caspase-1, IL-1β, IL-6, and TNF-α mRNA levels and protein density; on the other hand, IL-10 was increased, acting as a protector, preventing exacerbated inflammation. Under resveratrol exposure, P2X7 was negatively expressed, regulating inflammation to establish homeostasis and microglial proliferation. Additionally, resveratrol activates the A1 adenosine receptor, possibly correlated with neuroprotective effects. Conclusions: We confirmed the anti-neuroinflammatory action of resveratrol via the P2X7 receptor and NLRP3’s combined modulation, regulating the cell cycle and reducing pro-inflammatory and oxidant agents. Considering this pathway, resveratrol could be a candidate for further investigations as a potential treatment against neuroinflammatory diseases.